Behavioural Syndromes: Implications for Electrocommunication in a Weakly Electric Fish Species - Shank, Isabelle (Université d'Ottawa / University of Ottawa, 2013)
Behavioural syndromes, defined as suites of correlated behaviours across different contexts, are used to characterize individual variability in behaviours. Males of the weakly electric fish species, Apteronotus leptorhynchus, produce electro-communication signals called chirps. Chirps are thought to be involved in agonistic signalling, as their relative incidence increases during agonistic conspecific interactions. However, high levels of individual variability in aggression obscure the role of chirps in mediating aggression. Here, I tested the presence of an aggression-boldness behavioural syndrome, and then considered the implications such a syndrome would have on chirping behaviours. Behavioural tests in anti-predation, object novelty, feeding, conspecific intrusion and novel environment exploration contexts revealed a syndrome involving only object novelty and feeding. We found no correlation between chirping behaviour and the assessed behaviours. Our results demonstrate that chirps represent a more complex communication system than previously suggested.
Keywords: Principal Component Analysis; Electrocommunication; Behavioural Types; Boldness; Aggression; Weakly Electric Fish; Behavioural Syndromes; Apteronotus leptorhynchus